Academic Engagement, Academic Achievement, and Teacher Quality According to Gender: A Study with University Students from the Colombian Caribbean. (12th July 2018) - Donado, Antonio César; Zerpa, Carlos Enrique; Ruiz, Betty Luz
Abstract: This chapter reports a study that examines the differential effects of gender in teacher quality evaluations among Colombian students. Men and women rated teacher performance differently. Gender can be a moderating variable that better predicts the outcomes of such evaluations compared to commitment or academic performance.